A perspective on NETosis in diabetes and periodontal diseases - Valliammai Rajendran; Ashita Uppoor (Wolters Kluwer Medknow Publications, 2018)
Neutrophil-mediated immunity is the first host defense response against any infection. Crevicular efflux of neutrophils against bacteria is considered to be a novel defense mechanism in periodontal diseases. As a part of defense mechanism, neutrophils extrude its content and exhibit its antimicrobial activity by forming a web-like structure called neutrophil extracellular trap (NET) and undergo a process of cell death called NETosis. Under physiological conditions, NET production is limited and is balanced with its degradation, whereas NET production is found to be aggravated in chronic systemic inflammatory conditions such as diabetes mellitus and also in periodontal diseases. It is well known that a two-way relationship exists between diabetes mellitus and periodontal diseases. Interference in the process of NETosis might form a link between the two. The aim of this review is to focus on the potential role of NETosis in the pathogenesis of periodontitis and diabetes mellitus.